Legal Review of Parents in Facilitating Children Playing Jaran Kepang in View of Islamic Law and Law Number 35 of 2014 concerning Child Protection (Case Study of Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency) - Siti Nurheliza; Iwan (Warmadewa Press, 2024)
This study aims to understand the portrayal of the Jaran Kepang game and the perspectives of Islamic law and positive law on parents who facilitate their children playing Jaran Kepang in Sei Rotan Village. The research method employed is empirical research, which examines applicable legal provisions and the realities in Sei Rotan Village, Percut Sei Tuan Subdistrict, Deli Serdang Regency. The primary data for this research consists of observations and interviews with children who play Jaran Kepang, parents of Jaran Kepang players, the community of Sei Rotan Village, Jaran Kepang experts, and leaders/members of the Indonesian Ulema Council (MUI) North Sumatra. Secondary data sources include primary legal materials such as Law Number 35 of 2014 concerning Child Protection, and secondary legal materials obtained from literature review comprising books, journals, articles, internet searches, and research findings. The results indicate that some parents in Sei Rotan Village facilitate their children playing Jaran Kepang, as evidenced by interviews with the community and observations. The legal consequences for parents facilitating their children playing Jaran Kepang, according to Islamic law, are considered haram due to the game's association with polytheism. Under Law Number 35 of 2014 concerning Child Protection, the legal consequence is the potential revocation of custody rights for parents who facilitate their children playing Jaran Kepang.